Shifting Stacks (Atla Open Press, 2024)
Shifting Stacks examines emergent issues at the nexus of academic librarianship and theological education. It seeks to facilitate and inspire forward-thinking conversation that may guide a reorientation of theological and religious studies librarianship that is adaptive and responsive to change and emerging needs in librarianship, theological education, and the broader global community. The need for substantive conversation on these topics has grown more important and critical as the effects of the current global pandemic ripple through our institutions.